Political Culture: Concepts to Development of Thai Society. - Phathong, PhrakrupaladKetsada; Serirangsan, Thirapat; Dockthaisong, Boonton; Suwanabol, Issara (Journal of Graduate MCU KhonKaen Campus, 2019)
According to the article “Political Culture: Concepts to Development of Thai Society” the main purpose is to identify the characteristic of political culture, which is the relationship between the members of the political society and the political society in psychology. By which the political culture in which the political society wants is often instilled into the ideas, ideology, beliefs, etc. of members in that political society, depending on the politics of each country which may have different characteristics There are different countries leaders. But regardless of which country has a system of government, it needs stability. Because when the country is stable, it will result in good results in all aspects. This security can be achieved with stable political politics. With the characteristics of gradual urban development Security is related to the state power structure. Which each state may be different, therefore may not copy or style the country you want, in the context of Thai society, with Thai economic, social and political conditions There are changes every moment. As follows the political culture described in the content of the article, is therefore an alternative way to frame the study. Develop according to democratic ideology in Thai society.